Television match officials, referees, and home advantage: Evidence from the European Rugby Cup. Issue 3 (June 2020) - Dawson, Peter; Massey, Patrick; Downward, Paul
Highlights: 65% of European Rugby Cup group stages matches resulted in home wins. 64% of yellow cards awarded to away team in ERC. Crowd effects and referee experience key to home advantage in rugby. Television match official (TMO) has increased home advantage. Technology need not necessarily improve balance in decision making. Abstract: The regulation of on-field competition by officials is an important aspect of the management of sport. Increasingly, sports are providing technological support for officials to aid their decision making. In this paper, the authors analyse the impact of such an innovation by exploring the impact of the introduction and subsequent extended role of the television match official on the award of sanctionable offences of players in matches played in the group stages of the European Rugby Cup (ERC) and European Rugby Champions Cup (ERCC) over 15 seasons from 2000/01 to 2015/16. Rugby Union is an important sport to reflect upon because of the central role that the referee plays in rule interpretation and game management and the level of home advantage tends to be relatively high in the sport. Indeed, 65% of all matches in the sample analysed resulted in home wins. Results suggest that crowd effects and referee experience influence referee decisions, but the effects vary depending on the type of incident being considered. The main finding and contribution of the paper is that the introduction of the television match official has influenced the incidence of sanctions issued to both teams. However, the increase in the number of yellow cards awarded to away teams implies that home bias has increased since the introduction of the television match official. This suggests that referees may have been consciously or unconsciously seeking to avoid contributing to home bias before the introduction of a further official who is remote from the effects of the crowd. Recognising that such an adjustment takes place according to the circumstances is important information for the training of officials; particularly as a television match official may not be present in all games that they will referee.